Effect of rooibos extract (Aspalathus linearis) on lipid oxidation over time and the sensory analysis of blesbok (Damaliscus pygargus phillipsi) and springbok (Antidorcas marsupialis) droëwors. (May 2015) - Jones, Maxine; Hoffman, Louwrens C.; Muller, Magdalena
Abstract: The study objective was to investigate the addition of rooibos extract (RBE) in blesbok and springbok droëwors, a dried meat sausage with added beef fat, to improve oxidative stability. After a storage period of two weeks, inhibition of lipid oxidation showed to be successful with RBE 1.0% addition. No differences ( P > 0.05) in heme-iron results within the raw, dried or stored samples were seen. However, a positive correlation between lipid oxidation and heme-iron was noted. The fatty acid profiles suggest that after drying the decrease in polyunsaturated fats could be linked to the increase in lipid oxidation. Flavor and aroma differences between the varying RBE concentrations in the droëwors were detected by the sensory panel. A droëwors formulation using a combination of game meat and beef fat with the addition of RBE at a 1.0% concentration could be a successful addition to the processed meat market. Highlights: Study of addition of rooibos extract (RBE) to game droëwors to minimize oxidation. Lipid oxidation decreased significantly after storage period with addition of RBE 1.0%. Protein oxidation and heme-iron showed no significant differences with RBE addition. Sensory differences were detected with varying RBE concentrations.